2002
DOI: 10.1212/wnl.59.6.947
|View full text |Cite
|
Sign up to set email alerts
|

How often are nonenhancing supratentorial gliomas malignant? A population study

Abstract: The presence of contrast enhancement in a brain tumor is often regarded as a sign of malignancy. The authors identified 314 patients with malignant and low-grade supratentorial glial neoplasms in an unselected population, 58 of which lacked contrast enhancement on preoperative neuroimaging. Nonenhancing gliomas were malignant in approximately one third of cases, especially in older patients. Histologic confirmation of the diagnosis is therefore important in all patients suspected of harboring a primary glial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
211
2
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(228 citation statements)
references
References 8 publications
4
211
2
11
Order By: Relevance
“…Studies by Rollin et al 10 and Lam et al 21 failed to find a significant difference between the ADC values of high-grade and low-grade gliomas, and some studies have shown that tumor minimum ADC values have preoperative prognostic importance in patients with malignant supratentorial astrocytomas. 4,22,23 In addition, Barker et al 15 and Scott et al 16 demonstrated that the risk of anaplasia in nonenhancing cerebral tumors increases with age, whereas we did not find any difference between the ages of the patients with high-and low-grade astrocytomas.…”
Section: 10contrasting
confidence: 64%
“…Studies by Rollin et al 10 and Lam et al 21 failed to find a significant difference between the ADC values of high-grade and low-grade gliomas, and some studies have shown that tumor minimum ADC values have preoperative prognostic importance in patients with malignant supratentorial astrocytomas. 4,22,23 In addition, Barker et al 15 and Scott et al 16 demonstrated that the risk of anaplasia in nonenhancing cerebral tumors increases with age, whereas we did not find any difference between the ages of the patients with high-and low-grade astrocytomas.…”
Section: 10contrasting
confidence: 64%
“…This is likely because tumor enhancement results mainly from disruption of the blood-brain barrier, not tumor vascularity. 27,28 Our FA evaluation of the nonenhanced tumor components of grade IV tumors was likely affected by the fact we did not include areas in the brain that had high T2-weighted signal intensity but were ambiguous for representing tumor or only edema. This limited our analysis of nonenhanced components of grade IV tumors to n Ï­ 4.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 9% of HGGs are non-enhancing on post-gadolinium T1-weighted MR, which can be mistaken as low-grade gliomas [24]. Beppu et al showed that PCT measurement of BV could differentiate non-enhancing grade III gliomas from grade II gliomas with a sensitivity and specificity of 90.9% and 83.3%, respectively [15].…”
Section: G Modelmentioning
confidence: 99%